2007
DOI: 10.1029/2006gl028800
|View full text |Cite
|
Sign up to set email alerts
|

Variability of solar radiation under cloud‐free skies in China: The role of aerosols

Abstract: Analysis of long‐term surface global and diffuse solar radiation, aerosol single scattering albedo (SSA), and relative humidity (RH) data reveals that much of China experienced significant decreases in global solar radiation (GSR) and increases in diffuse solar radiation under cloud‐free skies between the 1960s and 1980s. With RH and aerosol SSA being rather constant during that time period, we suggest that the increasing aerosol loading from emission of pollutants is responsible for the observed reduced GSR a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

15
154
1
3

Year Published

2014
2014
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 187 publications
(173 citation statements)
references
References 23 publications
15
154
1
3
Order By: Relevance
“…In China, a decadal transition in SSR from dimming to brightening or at least a leveling off after approximately 1990 has also been reported (e.g., Liu et al 2004;Che et al 2005;Qian et al 2007Qian et al , 2011aShi et al 2008;Tang et al 2011). Changes in clouds cannot explain the dimming because more cloud-free sky has been observed (Qian et al 2006).…”
Section: Introductionmentioning
confidence: 98%
See 2 more Smart Citations
“…In China, a decadal transition in SSR from dimming to brightening or at least a leveling off after approximately 1990 has also been reported (e.g., Liu et al 2004;Che et al 2005;Qian et al 2007Qian et al , 2011aShi et al 2008;Tang et al 2011). Changes in clouds cannot explain the dimming because more cloud-free sky has been observed (Qian et al 2006).…”
Section: Introductionmentioning
confidence: 98%
“…The transition can be seen more distinctly when the radiative effects of cloud cover variability is removed (Allen et al 2013). Several studies have suggested that the increasing emissions of anthropogenic aerosols have resulted in less solar radiation reaching the ground (Che et al 2005;Qian et al 2006Qian et al , 2007Shi et al 2008;Wild 2009a). Moreover, researchers have suggested that changes in fuel utilization (Streets et al 2008) and, thus, in anthropogenic aerosol composition and associated single-scattering albedo (Qian et al 2007) may be responsible for the observed transition in SSR (Wild 2009a).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, using TOMS AOD at 500 nm along with MODIS AOD at 550 nm (2000)(2001)(2002)(2003)(2004)(2005)(2006)(2007)(2008), Guo et al (2011) observed a continuous upward trend in average AOD over eight typical regions across China without any transition in 1990. A significant increment of aerosol single-scattering albedo was reported in China between the early 1980s and 1998, which could result in less absorption and thus more radiation reaching the Earth's surface (Qian et al, 2007). The difference in the trends between PM concentrations and satellite AOD might be explained by the emission control policies in China, which target primary aerosols (mainly related to PM) but are less strict for secondary aerosol precursors (e.g., NO x , NMVOC, and NH 3 , mainly related to AOD; Lin et al, 2010).…”
Section: Evidence Of Urbanization Effects On Sunshine Variations In Cmentioning
confidence: 99%
“…Visibility throughout the world has generally decreased in recent decades, especially in Asia. In China, horizontal visibility has significantly decreased since 1980 (Che et al, 2007;Qian and Giorgi, 2000;Qian et al, 2007;Streets et al, 2008;Fu et al, 2013;Yang et al, 2016;Liu et al, 2016). For example, in Guangzhou, one of the largest cities in the Pearl River Delta (PRD), low visibility occurs on 150 days per year (Deng et al, 2008).…”
Section: Introductionmentioning
confidence: 99%